PENERAPAN METODE WATERFALL DALAM PEMBUATAN SISTEM INFORMASI DANA KAS KECIL PADA PT. NATUR PESONA INDONESIA - Puji Astuti (Evolusi : Jurnal Sains dan Manajemen, 2020)
The growing of a company, then the system used must follow the development of the Times, the role of technology in petrifying accounting process in a long-growing company, the main reason is efficiency, time saving, and cost. to achieve the results of the output of financial statements correctly PT. Natur Pesona Indonesia needs this one system. Because At PT. Natur Pesona Indonesia manages the financial records manually, from the acceptance, expense, and archiving of data that is still in progress with the process of acceptance and expense. Therefore, it is possible that when the process takes place error in recording, the less accurate report is made and delays in search of necessary data. The design of this information system is the best solution to solve the problems that exist in this company and with a computerized system can be achieved an effective and efficient activity in support of activities at PT. Natur Pesona Indonesia.  and with a computerized system an effective and efficient activity can be achieved in supporting activities at PT. Pesona Indonesia. A computerized system is better with method waterfall than a manual system to run more effectively and efficiently and a petty cash fund system that is now more conducive than the previous system.